The personal voice in biblical interpretation - Kitzberger, Ingrid Rosa (Routledge, 1998)
The Personal Voice in Biblical Interpretation makes evident the multiplicity and legitimacy of different interpretations and break new gound in the ongoing debate of the hermeneutics and methods in biblical scholarship.